Effect of olive cake in growing pig diets on fecal microbiota fermentation and composition - Belloumi, Dhekra; García-Rebollar, Paloma; Francino, P.; Calvet, Salvador; Jiménez-Belenguer, Ana; Piquer, Laia; Piquer, Olga; Cerisuelo, Alba (European Federation for Animal Science, 2023)
The intestinal microbiota plays a critical role in the metabolism and health of the host. The present study investigated the impact of two types of olive cake on short-chain fatty acid (SCFA) concentrations and the faecal microbiota composition of pigs. A total of 30 pigs (Landrace x Large white) with an initial body weight (BW) of 47.9±4.21 kg were divided into three groups according to the feed they received: control feed (C), feed with 200g/kg of partially defatted olive cake (PDOC) or feed with 200g/ kg of cyclone olive cake (COC). Faecal samples were collected from each animal after 3 weeks of the feeding trial.